Diversity and Diversification: Ecosystem Services Derived From Underutilized Crops and Their Co-benefits for Sustainable Agricultural Landscapes and Resilient Food Systems in Africa - Mabhaudhi, Tafadzwanashe; Hlahla, Sithabile; Chimonyo, Vimbayi Grace Petrova; Henriksson, Rebecka; Chibarabada, Tendai Polite; Murugani, Vongai G.; Groner, Vivienne P.; Tadele, Zerihun; Sobratee, Nafiisa; Slotow, Rob; Modi, Albert Thembinkosi; Baudron, Frédéric; et al. (Frontiers in Agronomy, 2022)
There are growing calls to adopt more sustainable forms of agriculture that balance the need to increase production with environmental, human health and wellbeing concerns. Part of this conversation has included a debate on promoting and mainstreaming neglected and underutilised crop species (NUS) because they represent a more ecologically friendly type of agriculture. We conducted a systematic review to determine the ecosystem services derived from NUS and assess their potential to promote functional ecological diversity, food and nutritional security, and transition to more equitable, inclusive, sustainable and resilient agricultural landscapes and food systems in Africa. Our literature search yielded 35 articles for further analysis. The review showed that NUS provides various provisioning, regulating, cultural, and supporting ecosystem services and several environmental and health co-benefits, dietary diversity, income, sustainable livelihood outcomes, and economic empowerment, especially for women. Importantly, NUS address the three pillars of sustainable development- ecological, social, and economic. Thus, NUS may provide a sustainable, fit-for-purpose transformative ecosystem-based adaptation solution for Africa to transition to more sustainable, healthy, equitable, and resilient agricultural landscapes and food systems.